Should HFrEF patients with NYHA class II expect benefit from CCM therapy?: Results from the MAINTAINED observational study - Fastner, Christian; Yücel, Gökhan; Hetjens, Svetlana; Rudic, Boris; Schmiel, Gereon; Toepel, Matthias; Liebe, Volker; Kruska, Mathieu; Borggrefe, Martin; Burkhoff, Daniel; Akın, Ibrahim; Dürschmied, Daniel; et al. (Clinical research in cardiology, 2022)
Background: Cardiac contractility modulation (CCM) is an FDA-approved device therapy for patients with refractory systolic heart failure and normal QRS width. Randomized trials demonstrated benefits of CCM primarily for patients with severe heart failure (> NYHA class II). Purpose: To better understand individualized indication in clinical practice, we compared the effect of CCM in patients with baseline NYHA class II vs. NYHA class III or ambulatory IV over the 5-year period in our large clinical registry (MAINTAINED Observational Study). Methods: Changes in NYHA class, left ventricular ejection fraction (LVEF), tricuspid annular plane systolic excursion (TAPSE), NT-proBNP level, and KDIGO chronic kidney disease stage were compared as functional parameters. In addition, mortality within 3 years was compared with the prediction of the Meta-Analysis Global Group in Chronic heart failure risk score. Results: A total of 172 patients were included in the analyses (10% with NYHA class II). Only patients with NYHA class III/IV showed a significant improvement in NYHA class over 5 years of CCM (II: 0.1 ± 0.6; p = 0.96 vs. III/IV: − 0.6 ± 0.6; p < 0.0001). In both groups, LVEF improved significantly (II: 4.7 ± 8.3; p = 0.0072 vs. III/IV: 7.0 ± 10.7%; p < 0.0001), while TAPSE improved significantly only in NYHA class III/IV patients (II: 2.2 ± 1.6; p = 0.20 vs. III/IV: 1.8 ± 5.2 mm; p = 0.0397). LVEF improvement was comparable in both groups over 5 years of CCM (p = 0.83). NYHA class II patients had significantly lower NT-proBNP levels at baseline (858 [175/6887] vs. 2632 [17/28830] ng/L; p = 0.0044), which was offset under therapy (399 [323/1497] vs. 901 [13/18155] ng/L; p = 0.61). Actual 3-year mortality was 17 and 26% vs. a predicted mortality of 31 and 42%, respectively (p = 0.0038 for NYHA class III/IV patients). Conclusions: NYHA class III/IV patients experienced more direct and extensive functional improvements with CCM and a survival benefit compared with the predicted risk. However, our data suggest that NYHA class II patients may also benefit from the sustained positive effects of LVEF improvement.
Gesehen am 10.07.2023